MODELING OF THE SOLUBILITY IN SUPERCRITICAL CARBON DIOXIDE OF SOME SOLID SOLUTE ISOMERS USING THE EXPANDED LIQUID THEORY. (Journal of Sciences & Technology, 2018)
One of the most important research fields of supercritical fluid technology is the solubility of solids in supercritical fluids. Solubility data is fundamental to the development of new supercritical applications as biodiesel production and refrigeration, and the enhancement of existing applications including environmental pollution, extraction and purification of pharmaceuticals, food and natural products, and natural gas industry. Hence, the ability to correlate and predict the solubility of solids in supercritical fluids is of utmost importance. In this work, we propose to correlate and predict the solubility in supercritical CO2 of disubstituted aromatic isomers of hydroxybenzoic acid with a new model based on the expanded liquid theory, in which the solid–fluid equilibrium is modeled using the local composition model of UNIQUAC in which the interaction parameters are related to the solvent reduced density with an empiric exponential form equations.  The experimental solubility data of o-hydroxybenzoic acid, p-hydroxybenzoic acid, m-hydroxybenzoic acid and mixed isomers (m-hydroxybenzoic acid+p-hydroxybenzoic acid) are used for evaluating the correlation and prediction capabilities of this new model. The results obtained using the proposed model show good agreement with the experimental data used.